Adsorption Equlibrium Of Phenols From Aqueous Solution Using Modified Clay. - Maarof, Hawaiah Imam; Hameed, Bassim H.; Ahmad, Abdul Latif (Institusi Jurutera Kimia Malaysia, 2003)
The adsorption equilibrium study of phenol, 3-chlorophenol and o-cresol from liquid-phase system was carried out at temperature of 30°C using modified montmorillonite.